Assessment of genetic variation in the Kedah Kelantan cattle using microsatellite markers - Bashir, Haytham Hago Abdelwahid; Panandam, Jothi Malar; Sharma, Reuben Sunil Kumar; Abdullah, Mohamad Hilmi (2009)
The Kedah Kelantan (KK) is the indigenous cattle breed of Malaysia and is mainly kept for meat production. The aim of this study was to assess the genetic variability in the KK using microsatellite markers. Six microsatellite loci HEL1, ETH225, ILSTS005, ILSTS006, INRA023 and INRA032, were amplified successfully in 36 of KK cattle. A total of 32 alleles were detected. The number of alleles per locus varied between 3 and 7 with an average of 5.33. The effective number of alleles (Ne) range between 1.99- 4.54 with average of 2.91. Expected heterozygocity was higher than the observed heterozygosity for all loci. The overall mean heterozygosity was 0.593 Observed heterozygosity ranged from 0.444 to 0.750. The values of inbreeding coefficient (FIS) based on the individual locus were positive for all loci except ETH225. Two loci (HEL1and ETH225) deviated from HWE equilibrium (p<0.05). This study shows that there is low genetic variability in the KK cattle.